Patterns of Cannabis Consumption, Social Networks, and Foraging. (January 2020) - Phillips, James G.; Evans, Mark; Hughes, Barry; Ogeil, Rowan P.
This study considered contextual factors (i.e., times, places, peers) associated with cannabis use. A total of 153 participants answered an anonymous online survey, completed the Cannabis Use Disorders Identification Test – Revised (CUDIT-R), and indicated their numbers of regular smoking partners, and times and places cannabis was normally purchased. Recent cannabis smokers had higher CUDIT-R scores and purchased cannabis from more places more often. Multiple regression considered subscales of the CUDIT-R. Greater cannabis consumption was associated with more smoking partners and purchases of cannabis at more times and places. Cannabis dependence was associated with cannabis purchases from more places and times and reports that there were more people prepared to do them favors. Harmful use was associated with more purchases at more locations. Patterns of cannabis foraging were compared with foraging behaviors previously observed for caffeine, nicotine, and alcohol. The data could inform the development and use of social media and location-aware services seeking to target risky substance use.